UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAN FRAKSI n-HEKSAN, ETIL ASETAT DAN AIR DARI SABUT KELAPA MUDA (Cocos nucifera Linn) TERHADAP Escherichia coli ESBL (Extended Spectrum Beta Lactamase) - Novia Dewi Purwaningrum; Lusia Murtisiwi; Diah Pratimasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Young coconut coir contains flavonoid compounds, phenols, tannins and saponins. The ethanol extract of young coconut coir was studied to have good antibacterial activity. This study aimed to see the inhibitory activity of ethanol extract compared fractions of young coconut coir ethanol extract in inhibiting Escherichia coli ESBL (Extended Spectrum Beta Lactamase) bacteria. Young coconut coir of extracted using 95% ethanol solvent of maceration method and patition using n-hexane and ethyl acetate solvent. Antibacterial activities using the diffusion method with concentrations of 25%, 50% and 75%. The negative control used DMSO 10%, while positve control used was chloramphenikol. Ethanol extract and fractions of ethanol extract of young coconut coir inhibited Escherichia coli ESBL bacteria. The largest radical inhibition zone was found in the ethyl acetate fraction with a concentration of 75% at 10.9 mm.